Creatine supplementation impairs airway inflammation in an experimental model of asthma involving P2 × 7 receptor. Issue 6 (18th April 2019) - Garcia, Monique; Santos‐Dias, Alana; Bachi, André Luis Lacerda; Oliveira‐Junior, Manoel Carneiro; Andrade‐Souza, Adilson Santos; Ferreira, Sérgio César; Aquino‐Junior, Jefferson Comin Jonco; Almeida, Francine Maria; Rigonato‐Oliveira, Nicole Cristine; Oliveira, Ana Paula Ligeiro; Savio, Luiz Eduardo Baggio; Coutinho‐Silva, Robson; et al.
Abstract: Creatine (Cr) is a substrate for adenosine triphosphate synthesis, and it is the most used dietary supplement among professional and recreative athletes and sportsmen. Creatine supplementation may increase allergic airway response, but the cellular and molecular mechanisms are unknown. We used murine model of OVA‐induced chronic asthma and showed that Cr supplementation increased total proteins, ATP level, lymphocytes, macrophages, and IL‐5 levels in BALF, as well as IL‐5 in the supernatant of re‐stimulated mediastinal lymph nodes. IL‐5 and IL‐13 expression by epithelial cells and by peribronchial leukocytes were increased by Cr. Cr augmented the expression of P2 × 7 receptor by peribronchial leukocytes and by epithelial cells, and increased the accumulation of eosinophils in peribronchial space and of collagen fibers in airway wall. In human cells, while Cr induced a release of ATP, IL‐6, and IL‐8 from BEAS‐2B cells, whole blood cells, such as eosinophils, and CD4 + T cells, P2 × 7 receptor inhibitor (A740003) reduced such effects, as denoted by reduced levels of ATP, IL‐6, and IL‐8. Therefore, Cr supplementation worsened asthma pathology due to activation of airway epithelial cells and peribronchial leukocytes, involving purinergic signaling. Abstract : Creatine monohydrate is the most used dietary supplement, mainly by athletes and sportsmen. After some reports showed that creatine supplementation can impair allergic response, the present study shows that pro‐allergic effects of creatine involves the impairment of airway inflammation and remodeling, linked to P2 × 7 receptor expression.